2013
DOI: 10.1016/j.neuroscience.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome complement influences functional callosal myelination

Abstract: In addition to androgen differences between males and females, there are genetic differences that are caused by unequal dosage of sex chromosome genes. Using the cuprizone-induced demyelination model, we recently showed that surgical gonadectomy of adult mice resulted in decreased normal myelination and remyelination compared to gonadally intact animals, suggesting a supporting role for sex hormones in the maintenance of myelination. However, inherent sex differences in normal myelination and remyelination per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 54 publications
(65 reference statements)
1
13
0
Order By: Relevance
“…Similar to previous observations, corpus callosum (CC) of EAE mice showed many periventricular infiltrating lesions around blood vessels and scattered throughout white matter, accompanied by microglia/macrophage and reactive astrocyte accumulation and fewer enhanced green fluorescent protein on the proteolipid promoter (PLP_EGFP + ) OLs (13,14). EAE CC pathology resembles that observed in EAE DC.…”
Section: Resultssupporting
confidence: 86%
“…Similar to previous observations, corpus callosum (CC) of EAE mice showed many periventricular infiltrating lesions around blood vessels and scattered throughout white matter, accompanied by microglia/macrophage and reactive astrocyte accumulation and fewer enhanced green fluorescent protein on the proteolipid promoter (PLP_EGFP + ) OLs (13,14). EAE CC pathology resembles that observed in EAE DC.…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, a study on brain development during puberty in adolescents demonstrated that sex steroids were related to sexual differences in the white matter microstructure . Moreover, sex chromosomes have been suggested to play a role in mediating the differential rates of remyelination observed in male and female mice . Although the exact mechanism of corpus callosum sexual dimorphism remains uncertain, we speculate that the maternal and placental gonadal hormones influence corpus callosum development.…”
Section: Discussionmentioning
confidence: 83%
“…42 Moreover, sex chromosomes have been suggested to play a role in mediating the differential rates of remyelination observed in male and female mice. 38,39 Although the exact mechanism of corpus callosum sexual dimorphism remains uncertain, we speculate that the maternal and placental gonadal hormones influence corpus callosum development. When neonates are disconnected from their mothers and the placenta, sexual dimorphism in the corpus callosum gradually becomes insignificant.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations